The Effect of the Predict-Discuss-Explain-Observe-Discuss-Explain (PDEODE) Learning Model on Students' Understanding of Physics Concepts in Temperature and Heat Material for Grade XI at SMAN 10 Bone - Jamal, A. Noorshafira Safitri; Sudirman; Ikbal, Muh. Syihab; Tiara (Impulse: Journal of Research and Innovation in Physics Education, 2026)
This research was motivated by the persistent gap in assessing students’ conceptual understanding, particularly on the topic of temperature and heat. Although the PDEODE learning model has been widely reported to improve learning outcomes, many previous studies have not examined indicators of conceptual understanding in depth or compared them comprehensively with conventional learning approaches. Therefore, this study aims to determine the differences in students’ understanding of physics concepts between those taught using the PDEODE model and those taught using conventional methods in grade XI at SMAN 10 Bone. This research employed a quasi-experimental design with a quantitative approach, specifically the Matching Only Posttest Control Group Design. The sample consisted of two classes selected through a two-step matching sampling technique, namely the experimental class and the control class. The research instrument was a multiple-choice test consisting of 20 validated items. Data were analyzed using both descriptive and inferential statistics, including normality tests, homogeneity tests, and hypothesis testing. The hypothesis test used was the Mann-Whitney test, which resulted in an Asymp Sig. (2-tailed) value of 0.049, indicating that the p-value is smaller than the significance level of 0.05. The findings revealed that the average conceptual understanding score of students in the experimental class was 68.12 (good category), while the control class scored 59.79 (moderate category). These results indicate that students taught using the PDEODE model demonstrated higher conceptual understanding. Therefore, it can be concluded that the PDEODE learning model positively influences students’ understanding of physics concepts.